The Role of Religiosity on Sustainable Consumption and Consumer Welfare Among Muslim Consumers - Al Hadi, M. Qoshid (STAI Serdang Lubuk Pakam, 2024)
Due to global challenges related to sustainability and environmental protection, Indonesian consumers, especially Muslims, are increasingly considering religiosity in their consumption decisions. This study aims to examine the role of religiosity on sustainable consumption and consumer welfare among Muslim consumers. Data were collected from 10 provinces in Indonesia with a majority Muslim population of 340 respondents. The results of the analysis through SmartPLS 3.0 show that extrinsic religiosity can moderate the relationship between sustainable consumption and consumer welfare. However, this is not the same as intrinsic religiosity which has a positive but insignificant relationship. Moreover, this study also found factors that build sustainable consumption, including product perception and consumer commitment to the environment among Muslim consumers in Indonesia. The findings suggest marketers to focus on strategies that integrate consumer religiosity and green product perceptions to support sustainable consumption. Marketers also need to educate consumers about green products for the sake of prosperity.